Abelhas sudoeste: cartografia de controvérsias na rede sociotécnica da meliponicultura - Lustosa, Priscila Rudiak (2021)
The present research was carried out with the general objective of analyzing the Sociotechnical Network from the cartography of controversies in the Southwest Abelhas group, in Paraná, following the meliponiculturists for a period of 12 months. The study was based on the theoretical and methodological contribution of the Actor-Network Theory (TAR), which makes it possible to understand meliponiculture in its multiple interrelationships. It began by identifying who makes up the actant collective: meliponiculturists; consumers; interested in the subject; scientists; stingless bees; predators; artifacts; plants; climate, among others. In the constant interrelationships between actants, the controversies that move the Network occur. The main “hot” controversies found were about: Management; Predators: lemon bee and Use of pesticides. In the course of the Network's cartography, four actants became keys in the composition of controversies and in the configuration of spokespersons: beekeepers A, B, C and D. These actants were followed through visits, interviews, observations, photographs, which sought to translate (translation as a process and not as a result) the dynamics of the interrelationships of the group of meliponiculturists and the way of existence of stingless bees, getting directly involved in the controversies. It was found that meliponiculture is a recent activity in the region and that it is growing, as there are still many people who do not know the stingless bees or their ecological, social and economic role. Thus, it emphasizes the importance of meliponiculture in the Southwest region of Paraná and the power of an Association to promote studies and sustainable practices, in the interrelationships between human actants, stingless bees, plants, tools, among others.